Acellular Nipple Scaffold Development, Characterization, and Preliminary Biocompatibility Assessment in a Swine Model. Issue 4 (6th December 2022) - Oganesyan, Ruben V.; Lellouch, Alexandre G.; Acun, Aylin; Lupon, Elise; Taveau, Corentin B.; Burlage, Laura C.; Lantieri, Laurent A.; Randolph, Mark A.; Cetrulo, Curtis L.; Uygun, Basak E.
Abstract : Background: The standard in nipple reconstruction remains the autologous skin flap. Unfortunately, the results are not satisfying, with up to 75% loss of nipple projection over time. Existing studies investigated the use of primates as a source of implants. The authors hypothesized that the porcine nipple can serve as a perfect shape-supporting implant because of functional similarities to the human nipple. A decellularization protocol was developed to obtain an acellular nipple scaffold (ANS) for nipple reconstruction. Methods: Tissue samples were collected from eight disease-free female Yorkshire pigs (60 to 70 kg) and then decellularized. The decellularization efficiency and extracellular matrix characterization was performed histologically and quantitatively (DNA, total collagen, elastin, and glycosaminoglycan content). In vitro and in vivo biocompatibility was determined by human dermal fibroblast culture and subcutaneous implantation of six ANSs in a single Yorkshire pig (60 to 70 kg), respectively. Inflammation and adverse events were monitored daily based on local clinical signs. Results: The authors showed that all cellular structures and 96% of DNA [321.7 ± 57.6 ng DNA/mg wet tissue versus 11.7 ± 10.9 ng DNA/mg wet tissue, in native and ANS, respectively ( P < 0.001)] can be successfully removed. However, this was associated with a decrease in collagen [89.0 ± 11.4 and 58.8 ± 9.6 μg collagen/mg ( P < 0.001)] and elastin [14.2 ± 1.6 and 7.9 ± 2.4 μg elastin/mg ( P < 0.05)] and an increase in glycosaminoglycan content [5.0 ± 0.7 and 6.0 ± 0.8 ng/mg ( P < 0.05)]. ANS can support continuous cell growth in vitro and during preliminary biocompatibility tests in vivo. Conclusion: This is a preliminary report of a novel promising ANS for nipple reconstruction, but more research is needed to validate results. Clinical Relevance Statement: Breast cancer is very common among women. Treatment involves mastectomy, but its consequences affect patient mental well-being, and can lead to depression. Nipple-areola complex reconstruction is critical, and existing methods lead to unsatisfactory outcomes.